The YrbE phospholipid transporter of Salmonella enterica serovar Typhi regulates the expression of flagellin and influences motility, adhesion and induction of epithelial inflammatory responses. (3rd May 2020) - Verma, Smriti; Prescott, Rachel A.; Ingano, Laura; Nickerson, Kourtney P.; Hill, Emily; Faherty, Christina S.; Fasano, Alessio; Senger, Stefania; Cherayil, Bobby J.
ABSTRACT: Salmonella enterica: serovar Typhi is the etiologic agent of typhoid fever, a major public health problem in the developing world. Moving toward and adhering to the intestinal epithelium represents key initial steps of infection by S . Typhi. We examined the role of the S . Typhi yrbE gene, which encodes an inner membrane phospholipid transporter, in these interactions with epithelial cells. Disruption of yrbE resulted in elevated expression of flagellin and a hypermotile phenotype. It also significantly reduced the ability of S . Typhi to adhere to the HeLa epithelial cell line and to polarized primary epithelial cells derived from human ileal organoids. Interestingly, the yrbE -deficient strain of S . Typhi induced higher production of interleukin-8 from the primary human ileal epithelial cell monolayers compared to the wild-type bacteria. Deletion of the flagellin gene ( fliC ) in the yrbE -deficient S . Typhi inhibited motility and attenuated interleukin-8 production, but it did not correct the defect in adhesion. We also disrupted yrbE in S . Typhimurium. In contrast to the results in S . Typhi, the deficiency of yrbE in S . Typhimurium had no significant effect on flagellin expression, motility or adhesion to HeLa cells. Correspondingly, the lack of yrbE also had no effect on association with the intestine or the severity of intestinal inflammation in the mouse model of S . Typhimurium infection. Thus, our results point to an important and serovar-specific role played by yrbE in the early stages of intestinal infection by S . Typhi.